Water Quality Meter Module to improve shrimp production quality in Mojopuro Gede Village, Gresik - Firnanda Pristiana Nurmaida; Agus Indra Gunawan; Dananjaya Endi Pratama; Fithrotul Irda Amaliah; Fildzah Aure Gehara Zhafirah; Muhammad Wafiq Kamaluddin; Ari Setiawan; Nashrullah Nashrullah; Alfandino Rasyid (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
Shrimp cultivation is a very profitable business in Gresik. However, shrimp farmers in Mojopuro Gede Village, Gresik admitted that they did not optimize their cultivation process. The farmer did not realize that water quality is essential to be considered in aquaculture. Based on these problems, the team held a community service in Mojopuro Gede Village, Gresik by introducing the water quality meter module and giving it to several shrimp farmers in the area. This activity was carried out so that the farmers can improve their cultivation process which has not been optimal and also introduce them to technological developments. Technology use in cultivation is expected to increase the quality of the farmers' crops. The implementation methods used in this activity are socialization and training. In this community service program, education has been given to the farmers so that they understand and care about the condition of their ponds in the cultivation process. The purpose of this program is for introducing the importance of technology in the cultivation process, even though it is actually not easy to provide education to shrimp farmers, especially traditional farmers. Therefore, related parties (NU Gresik Maritime Institute and Maritime Affairs and Fisheries Office of East Java Province) are expected to be more active in providing understanding to the farmers regarding the importance of applying technology in the cultivation process.